Utilisation of earthworm meal in partial replacement of soybean and fish meals in diets of broilers - Loh, Teck Chwen; Fong, L. Y.; Foo, Hooi Ling; Thanh, N. T.; Abdul Rahman, Sheikh Omar (GSP, India, 2009)
To study the effect of worm meal (WM) as partial replacement of soybean and fish meals in the diets, a total of 245 day-old broiler chicks were randomly assigned to five different treatment groups (0%, 5%, 10%, 15% and 20% WM) in partial replacement of soybean and fish meals for a period of 6 weeks. The final body weight, growth rate and feed efficiency of the 10% and 15% WM groups broiler were better (P<0.05) than that of the control group with no effect on feed intake. The digestibility of crude protein for WM was 63%. 10% WM group gave a higher (P<0.05) lactic acid bacteria counts and showed no significant difference (P>0.05) in Enterobacteriaceae count or fecal pH. These results suggest that WM could be used to replace soybean and fish meals between 10 to 15% in broiler diets.